Commonwealth of Independent States and the Middle East - Merkaz le-ḥeḳer Beri. ha-M. u-Mizraḥ Eropah 'a. sh. Marg’ori Meiroḳ. (Marjorie Mayrock Center for Soviet and East European Research, the Hebrew University, 1992)
Continues: Soviet Union and the Middle East, ISSN 0334-4142.